Analisis Kinerja Pelayanan Penyuluh Pertanian Pada Dinas Ketahanan Pangan, Tanaman Pangan dan Hortikultura Majalengka Terhadap Kepuasan Petani Tanaman Padi di Kabupaten Majalengka - Bajuri, Diding; Sari, Jayantie Diana; Rezka, Ria (Universitas Bandar Lampung (UBL), 2024)
This study evaluates the performance of agricultural extension officers at the Food Security, Crop, and Horticulture Office of West Java Province in relation to the satisfaction of rice farmers in Majalengka Regency. Using a descriptive qualitative approach, the findings indicate that extension officers who provide accurate, responsive, and relevant technical information significantly enhance farmer satisfaction, despite challenges such as a limited number of officers, difficult access in remote areas, and insufficient attention to farmers' socioeconomic conditions. Key factors influencing satisfaction include accessibility, service frequency, and the relevance of extension materials, with farmers receiving regular services and personalized approaches reporting higher satisfaction and productivity increases of up to 20%. To improve service quality, the study recommends increasing the number of extension officers, ensuring equitable distribution, implementing continuous training, and adopting approaches that better address farmers' social and economic needs.